OPTIMASI SUHU DAN WAKTU PENGERINGAN KOPRA PUTIH DENGAN PEMANASAN TIDAK LANGSUNG (INDIRECT DRYING) - Vina Agustini; Burhan Burhan; Askur Rahman (Agroindustrial Technology, University of Trunojoyo Madura, 2014)
Copra drying process conventionally carried out by using sundrying and fogging. The weakness of these methodsis that copra is easily contaminated by dust, gravel and microbes, thus resulted in low quality product. Drying in a dryer results in better quality copra with white colour of flesh. The purpose of this study was to determine the optimum drying temperature and time to result in white copra that meetsquality standards as indicated by water, oil and free fatty acid content. Experiment design was done by employing Response Surface Methodology (RSM) and Central Composite Rotatable Design (CCRD) with 2 factor, 5 levels for each factor, and total of 13 treatments. The results showed that optimum time for dryingwas13 hours at temperature in 60-66°C. Copra resulted had water content of 2.66%, oil content of 61.5% and free fatty acid content of 0.63%. The copra produced showed brown colour which may be related to temperature and drying time used in the process